Differences in the lipid metabolism profile and clinical characteristics between eosinophilic and non-eosinophilic acute exacerbation of chronic obstructive pulmonary disease - Wang, Yating; Chang, Chun; Tian, Sifan; Wang, Juan; Gai, Xiaoyan; Zhou, Qiqiang; Chen, Yahong; Gao, Xu; Sun, Yongchang; Liang, Ying (Frontiers in Molecular Biosciences, 2023)
Objective: In this study, we aimed to investigate the difference of serum lipid metabolites profiles and its relationship with clinical characteristics between patients with eosinophilic and noneosinophilic AECOPD.Methods: A total of 71 AECOPD patients were enrolled. Eosinophilic AECOPD was defined as blood EOS%≥2% (n = 23), while non-eosinophilic AECOPD with blood EOS＜2% (n = 48).Clinical data were collected, and serum lipid metabolism profiles were detected by liquid chromatography-mass spectrometry (LC-MS). The XCMS software package was used to preprocess the raw data, then lipid metabolites identification was achieved through a spectral match using LipidBlast library. Differences of lipid profiles and clinical features between eosinophilic and non-eosinophilic group were analyzed by generalized linear regression. The Least Absolute Shrinkage and Selection Operator (LASSO) was applied to screen the most characteristic lipid markers for eosinophilic phenotype.Results: Eosinophilic AECOPD patients had less hypercapnic respiratory failure, less ICU admission, shorter length of stay in the hospital, and lower fibrinogen level. In the lipid metabolism profiles, 32 significantly different lipid metabolites were screened through t-test adjusted by FDR (FDR-adjusted p<0.05 and VIP>1). 9 differential lipid metabolites were found to be associated with the three clinical features, hypercapnia respiratory failure, ICU admission, and fibrinogen in further integration analysis. The species of triacylglycerol (TAG), phosphatidylcholine (PC), lysophophatidylcholine (LPC) and diacylglyceryl trimethylhomoserine (DGTS) were higher in those eosinophilic AECOPD. The LASSO was applied and 3 lipid metabolites were retained, which were LPC (16:0), TAG (17:0/17:2/17:2), LPC (20:2). Logistic regression model was fitted using those three markers, and the area under the ROC curve of the model was 0.834 (95%CI: 0.740-0.929).Patients with eosinophilic AECOPD had a unique lipid metabolism status. Species of TAGs and LPCs were significantly increased in this phenotype and was associated with better clinical outcomes.